Supply chain management among SMEs in Klang Valley, Malaysia: the possibilities and the challenges - Joyce F.Y. Leu; Ridzuan Masri (International Journal of Supply Chain Management, 2019)
Abstract- Over the years, the issue of talent shortage and undermanage of talent continues to stir challenges to many organizations both large and smaller firms. In most cases, SMEs constantly suffer from the shortage of talent due to various internal constraints, however, SMEs do aware of the importance of getting the right people for the key positions. Many of the respondents do recruit domain experts, although these employees are in the categories of lower-skilled workers. Although some forms of informal training provided by most SMEs to their employees, and tie the compensation with a merit-pay system, nevertheless, further alignment between skilled-workers and business goals still need to be enhanced in the long run. Despite all challenges and limitations, it is still possible for SMEs to kick-start proper talent management systems and continuously improves it from time to time. Identifying key positions is an initial attempt of talent management, as firms only need to hire talents in the area of a few core job functions. Followed by this will be appropriate talent development and commitment of firms to align talents with business goals. Also, inspiriting work cultures and values, proper feedback systems, and the like will further enhance the branding of SMEs and make it easier for SMEs to attract and retain talents. All these efforts will eventually translate into desirable organizational strategic outcomes.